2019
DOI: 10.1103/physrevlett.122.257401
|View full text |Cite
|
Sign up to set email alerts
|

Resolving Continua of Fractional Excitations by Spinon Echo in THz 2D Coherent Spectroscopy

Abstract: We show that the new technique of terahertz 2D coherent spectroscopy is capable of giving qualitatively new information about fractionalized spin systems. For the prototypical example of the transverse field Ising chain, we demonstrate theoretically that, despite the broad continuum of excitations in linear response, the 2D spectrum contains sharp features that are a coherent signature of a "spinon echo", which gives previously inaccessible information such as the lifetime of the two-spinon excited state. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 34 publications
(107 reference statements)
0
55
0
Order By: Relevance
“…Unfortunately, the ground states of these systems cannot be easily captured by experiment, remaining featureless to conventional local probes. A promising route to detect QSLs is to look for signatures of fractionalization in dynamical probes, such as inelastic neutron scattering [13][14][15][16][17][18], Raman scattering [19][20][21][22][23][24][25], resonant inelastic x-ray scattering [26,27], ultrafast spectroscopy [28], and two-dimensional (2D) terahertz nonlinear coherent spectroscopy [29].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the ground states of these systems cannot be easily captured by experiment, remaining featureless to conventional local probes. A promising route to detect QSLs is to look for signatures of fractionalization in dynamical probes, such as inelastic neutron scattering [13][14][15][16][17][18], Raman scattering [19][20][21][22][23][24][25], resonant inelastic x-ray scattering [26,27], ultrafast spectroscopy [28], and two-dimensional (2D) terahertz nonlinear coherent spectroscopy [29].…”
Section: Introductionmentioning
confidence: 99%
“…While various dynamical probes [9,14,[30][31][32][33][34] have been exploited in several materials to look for signatures of spin fractionalization and their proximity to the Kitaev QSL, employing phonon dynamics and the spin-lattice coupling to detect Kitaev QSL is less investigated. It was recently suggested that sound attenuation from the phonon decaying into a pair of Majorana fermions [35][36][37] and the Hall viscosity induced by time-reversal breaking spin Hamiltonian [36,37] may potentially serve as such probe.…”
mentioning
confidence: 99%
“…The absence of sharp signatures has hampered the progress in the discovery of quantum spin liquids.In this paper, we consider two-dimensional nonlinear spectroscopy as a tool to detect distinctive signatures of fractionalized quasiparticles in quantum spin liquids. The current work is motivated by a previous work that shows how the domain wall excitations in the transverse field Ising model can clearly be detected in twodimensional THz spectroscopy [5]. Here we consider the exactly solvable Kitaev spin liquids on the honeycomb lattice [6] and investigate the signatures of Majorana fermions and fluxes in the two-dimensional spectroscopy.…”
mentioning
confidence: 99%
“…The third order susceptibilities in Eqs. (5) and (6) are calculated from the four-point correlation functions R (l=1,2,3,4),z zzz , which are expanded from the nested com-mutators in Eq. (7) [7]:…”
mentioning
confidence: 99%